Replication deficiencies in priA mutants of Escherichia coli lacking the primosomal replication n' protein. - Lee, E H (1991)
The priA gene of Escherichia coli encodes the protein that initiates assembly of the promosome, the entity essential for the replication of phage phi X174 and ColE1-like plasmids in vitro. We have prepared a null priA mutant to assess its role in vivo in replication of phages, plasmids, and the host chromosome. Extracts of this mutant are inert in the initial conversion of the phi X174 viral strand to the duplex form, confirming the absence of the PriA activity. In vivo, the priA mutant fails to produce phi X174 phage and, remarkably, is unable to maintain plasmids that depend on the E. coli chromosome origin as well as those of ColE1. Deficiencies in cell growth and cell division are also manifest.